Stages of madness : representations of madness in Shakespeare's Richard II, Hamlet and Macbeth - Power, Andrew J. (Trinity College (Dublin, Ireland). School of English, 2006)
This thesis is divided in six chapters that are grouped in pairs. The first, third, and fifth chapters deal with a single theoretical area of influence on the perception of madness in Shakespeare’s time and provide contextual material for the ensuing chapter. The second, fourth, and sixth chapters each offer a reading of a single play in the light of the theoretical and contextual chapters that precede them in the thesis. The opening chapter of the thesis, ‘Self Made Man,’ investigates the increasing subjectivity of characters on the English stage up to and during the renaissance, (engaging with the biblical pageants, medieval moral allegorical drama and Tudor moral interludes). It further investigates medieval religious means of attaining self- knowledge (and most importantly what it means to lose self-knowledge) as evident in penitential and other religious literature in the medieval period and draws new conclusions about the influence this literature had on the medieval and renaissance stage.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin